Effect of ouabain and metabolic inhibitors on the Na and K movements of nucleotide contents of L cells - Lamb, J. F. (1971)
1. The general characteristics and Na and K movements of L cells (derived from mouse epithelium) have been measured. Both cells grown in suspension (LS cells) and as a monolayer (L cells) were used. 2. The volume of L cells was 1·2 × 10(-9) cm(3) and of LS cells 3·5 × 10(-9) cm(3); of this 82% was water. 3. Electron micrographs showed the presence of numerous protrusions (filopodia) from both forms of the cell. These had the effect of increasing the surface area of the cell by 2-4 times over smooth cells of the same volume. On changing from the flattened to the spherical shape during trypsinization, the filopodia altered to maintain a constant V/A ratio. 4. These cells contain K, about 170 m-mole/l. intracellular water and Na, 9 m-mole/l. intracellular water (L cells only) at 20° C. The K fluxes are 1·9 p-mole/cm(2) sec for LS cells and 0·8 p-mole/cm(2) sec for L cells and the Na fluxes are 1·8 p-mole/cm(2) sec for L cells (expressed as per total cell surface (including filopodia)). If expressed as p-mole/cell per sec then L and LS cells have the same K flux. 5. 10(-4) M ouabain reduces the K influx to half, indicating an insensitivity to the glycosides common to the species. In the prolonged presence of ouabain the cells come into a new steady state with a [K](1), of 140 and a [Na](1) of 20-30 m-mole/l. intracellular water, but a constant [Na + K](1). 6. Both DNP (10(-3) M) and IAA (10(-4) M) are required for maximum inhibition of K uptake, as both aerobic and anaerobic metabolic pathways may be used to drive the pump. 7. K removal decreases the Na efflux, and Na removal (eventually) decreases the K influx providing evidence for Na/K coupling. 8. The cells contain 7·5 m-mole/litre intracellular water of ATP, a level some 15 times that of ADP. 9. The Na pump in these cells is very similar to that found in other tissues in that (a) it requires K to work, (b) it is blocked by ouabain and metabolic inhibitors and (c) it transports three molecules of Na for each two molecules of K.